Overview of Sleep Quality in Active Smoking Adolescents in Denpasar City - Putra, Made Rangga Dwinanta; Permatananda, Pande Ayu Naya Kasih; Udiyani, Desak Putu Citra; Aryastuti, Anak Agung Sri Agung; Cahyawati, Putu Nita (PT FORMOSA CENDEKIA GLOBAL, 2026)
Poor sleep quality is a common health problem among adolescents, and smoking is known to worsen sleep quality. Nicotine, as a stimulant, can disrupt sleep patterns, prolong sleep latency, and reduce sleep efficiency. Denpasar City has a relatively high prevalence of adolescent smokers; however, data regarding the sleep quality of active adolescent smokers remain limited. This study aimed to describe the sleep quality of active adolescent smokers in Denpasar City. This study employed a descriptive observational design with a cross-sectional approach. The results showed that most respondents were male (80.3%), all were late adolescents aged 18–24 years (100%), and the most commonly used type of cigarette was electronic cigarettes (47%). More than half of the respondents had poor sleep quality (56.1%). In conclusion, the majority of active adolescent smokers in Denpasar City are male late adolescents, with electronic cigarettes being the most commonly consumed tobacco product. Most respondents demonstrated poor sleep quality. These findings highlight the impact of smoking on adolescent sleep quality and may support promotive and preventive efforts to improve adolescent sleep health in Denpasar City.